The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2013
DOI: 10.1128/iai.00834-12
|View full text |Cite
|
Sign up to set email alerts
|

Beclin 1 Is Required for Starvation-Enhanced, but Not Rapamycin-Enhanced, LC3-Associated Phagocytosis of Burkholderia pseudomallei in RAW 264.7 Cells

Abstract: LC3-associated phagocytosis (LAP) of Burkholderia pseudomallei by murine macrophage (RAW 264.7) cells is an intracellular innate defense mechanism. Beclin 1, a protein with several roles in autophagic processes, is known to be recruited to phagosomal membranes as a very early event in LAP. We sought to determine whether knockdown of Beclin 1 by small interfering RNA (siRNA) would affect recruitment of LC3 and subsequent LAP of infecting B. pseudomallei. Both starvation and rapamycin treatment can induce Beclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…More recently we have extended our analysis of B. pseudomallei infection of RAW macrophages to examining rapamycin or starvation treatment on the consequences for LAP in the presence of BECN1 knockdown (by siRNA). Although we observed enhanced LAP of B. pseudomallei in both cases, rapamycin‐elicited Beclin 1‐independent LAP whereas the starvation response was Beclin 1 dependent 19 . The significance of this finding is currently under further investigation.…”
Section: Autophagic Processes and B Pseudomalleimentioning
confidence: 51%
“…More recently we have extended our analysis of B. pseudomallei infection of RAW macrophages to examining rapamycin or starvation treatment on the consequences for LAP in the presence of BECN1 knockdown (by siRNA). Although we observed enhanced LAP of B. pseudomallei in both cases, rapamycin‐elicited Beclin 1‐independent LAP whereas the starvation response was Beclin 1 dependent 19 . The significance of this finding is currently under further investigation.…”
Section: Autophagic Processes and B Pseudomalleimentioning
confidence: 51%
“…It has been demonstrated that LC3 can also be recruited to single membrane phagosomes or vesicles to assist in lysosomal fusion in a process denoted as LC3-associated phagocytosis (LAP) (73)(74)(75)(76). Pathogens such as Burkholderia pseudomallei and Mycobacterium marinum have elicited LAP features in RAW264.7-GFP-LC3 macrophages (77)(78)(79). There is no clear indicator of LAP; however, there has been a universal consensus that the ATG5-ATG12-ATG16L1 complex is required for LAP induction (75,80,81).…”
Section: Discussionmentioning
confidence: 99%
“…In microautophagy, portions of the cytoplasm are engulfed by invagination, protrusion and fission of the lysosomal membrane for a review see (Mijaljica and Devenish, 2011; Li et al, 2013). In contrast, in CMA unfolded and soluble proteins are translocated directly across the limiting membrane of the lysosome.…”
Section: The Autophagic Pathwaymentioning
confidence: 99%
“…In contrast, autophagy stimulation by rapamycin treatment enhances the targeting of B. cepacia to the lysosomal compartment. (Abdulrahman et al, 2011; Li et al, 2013) In addition, it has been shown that B. cepacia inactivates the small GTPase Rab7 (Huynh et al, 2010), a key molecule required for the maturation and completion of the autophagic pathway (Jager et al, 2004; Gutierrez et al, 2005). Thus, inactivation of this Rab protein is part of the strategy used by B. cepacia to avoid autophagic clearance.…”
Section: Xenophagy: Antibacterial Autophagymentioning
confidence: 99%